Bromophosphoalkoxylation of olefins with organic phosphates, cyclic ethers and NBS. Issue 5 (4th February 2016) - Sohail, Muhammad; Peng, Chang; Ning, Siyang; Zhang, Yixin; Khan, Muhammad; Zhao, Zongbao K.
Abstract: A variety of structurally novel phosphoalkoxy ester derivatives were prepared via highly regio- and diastereoselective four-component reaction involving olefin, cyclic ether, halogen reagent and organic phosphate. All components can be varied flexibly and moderate to excellent yields were obtained at room temperature. Several of these ester derivatives showed strong anticancer activity against human lung adenocarcinoma cells. Graphical abstract: